2018
DOI: 10.1103/physrevx.8.021067
|View full text |Cite
|
Sign up to set email alerts
|

Operando Imaging of All-Electric Spin Texture Manipulation in Ferroelectric and Multiferroic Rashba Semiconductors

Abstract: The control of the electron spin by external means is a key issue for spintronic devices. Using spin-and angle-resolved photoemission spectroscopy (SARPES) with three-dimensional spin detection, we demonstrate operando electrostatic spin manipulation in ferroelectric α-GeTe and multiferroic Ge 1−x Mn x Te. We demonstrate for the first time electrostatic spin manipulation in Rashba semiconductors due to ferroelectric polarization reversal. Additionally, we are also able to follow the switching pathway in detail… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 38 publications
6
40
0
1
Order By: Relevance
“…The P-E loops were measured in dual AC resonance tracking. It follows that both instrumental setups deliver consistent results, in agreement with published results [6,7,23].…”
Section: Fe Domains Probed By Piezo-force Scanning Microscopysupporting
confidence: 90%
See 1 more Smart Citation
“…The P-E loops were measured in dual AC resonance tracking. It follows that both instrumental setups deliver consistent results, in agreement with published results [6,7,23].…”
Section: Fe Domains Probed By Piezo-force Scanning Microscopysupporting
confidence: 90%
“…Moreover, the magnetic impurities open up a Zeeman gap at the Dirac point, making this the first 3D system to possess a Rashba-Zeeman type spin splitting with clear multiferroic hysteretic properties [9,22]. State-of-the-art operando spin-resolved photoemission results from Ge 0.87 Mn 0.13 Te showed that manipulation of both the Rashba and magnetic spin polarization upon switching of the ferroelectric polarization is possible, thereby demonstrating a strong magnetoelectric coupling with magnetoelectic functionality entangled with the Rashba-type spin texture [23].…”
Section: Introductionmentioning
confidence: 96%
“…Having localized the -GeTe bulk Rashba-type bands, following the concept proposed by D. Di Sante et al [1], the reversal of the ferroelectric polarization should also revert the spin helicity. In order to demonstrate this, we performed operando SARPES measurements for -GeTe films grown on conductive InP substrates by using a top-gate structure to enable application of an electric field during SARPES measurement [11]. By monitoring the spin texture in ultra-high vacuum via SARPES, upon application of voltages across the film and enabling the detection of photoelectrons across an Au-grid placed on top of the sample surface, we found that the spin texture is indeed influenced and changes direction for opposite voltage polarity.…”
Section: -Gete Rashba-type Spin Texturementioning
confidence: 99%
“…One of the reasons is that a large enough free charge carrier concentration will cause the ferroelectric order to break down, although where this limit lies is still an open question [1][2][3]. Recently, it was shown that the atomic displacement and inversion symmetry breaking associated with ferroelectric order leads to a switchable Rashba-type spin splitting of the bulk bands in semiconducting GeTe [4][5][6]. This raises the question as to what will happen to electronic states at the Fermi level of a ferroelectric material based on transition metal oxides (TMOs) with low enough free charge density, or for a conductive material in close proximity to such a ferroelectric.…”
Section: Introductionmentioning
confidence: 99%